Strategi Pengembangan Kurikulum 2013 Pendidikan Agama Islam Berbasis Multikultural di SMPN 1 Garut - Suhana Suhana; Uus Ruswandi; Bambang Samsul Arifin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
Phonemena the emergence of ethnic and religious conflicts is one of them due to the lack of insight into understanding of cultural diversity that should be an inevitability. Responding to this, Islamic Religious Education is important to be developed in multicultural insight so that the reality of multicultural society can be accommodated in it. This research uses a qualitative approach with this type of case study, with the location of. Research in SMPN 1 Garut West Java. The informant of this study is pai principal and teacher, with data retrieval methods through interviews, observations and documentation studies. Dor implementation of the research, what results are obtained, and the benefits of the research. The data that has been obtained is analyzed, interpreted and interpreted in a descriptive quality. The results of the findings obtained are the formulation of pai curriculum that is applied is flexible and based on the analysis of the situation faced by the community. Pai's design takes into account the multicultural aspects of society by paying attention to the situation of students, and teachers who carry out learning activities. The strategy used is to include multicultural values such as a sense of justice, love, and compassion, mutual respect both between teachers and students, between school institutions and elements in the school and with the community.